Postmortem Computed Tomography and Computed Tomography Angiography: Cardiothoracic Imaging Applications in Forensic Medicine. Issue 5 (September 2019) - Lee, Heon; Lee, Sookyoung; Cha, Jang Gyu; Baek, Taehwa; Yang, Kyung-moo
Abstract : With the introduction of modern imaging technology into the forensic field, postmortem imaging, particularly postmortem computed tomography (PMCT), has gained increasing importance in forensic investigations of deaths. In recent years, PMCT, which aims to provide observer-independent, reproducible forensic assessment in a minimally invasive manner, has been incorporated into routine forensic practice in many medicolegal institutions worldwide as a complement to autopsy. To address questions with regard to vascular pathologies, postmortem computed tomography angiography (PMCTA) has been developed and has become a useful tool for exploring the vascular system. Currently, these techniques play roles in screening for potential pathologies for later autopsy confirmation, facilitating focused dissection of the target area, and visualizing lesions that would be difficult or impossible to detect during autopsy. Adequate image interpretation requires knowledge and understanding of postmortem changes in the body and artefacts related to PMCT and PMCTA. This article reviews the PMCT and PMCTA techniques in terms of their indications, applications, advantages, and limitations for cardiothoracic applications. Our findings will enhance readers' understanding of emerging CT techniques in forensic radiology.